Twice buried - Havill, Steven frey50 (Scottsdale, AZ Poisoned Pen Press, 2000)
In New Mexico, Undersheriff Bill Gastner investigates the death of a real estate agent with the help of Estelle Reyes-Guzman, the prime suspect's niece.
Keywords: Gastner, Bill (Fictitious character); Sheriffs; New Mexico; Detective and mystery stories